Lumbar disc herniation modelling: a review of ex-vivo mechanical models and a comparison with clinical data - Slater,T; Wilke,H-J; Gurusamy,G; Rajasekaran,S; Newell,N (European Spine Journal, 2025)
PurposeEx-vivo herniation models are essential for studying lumbar disc herniation mechanisms, but their morphological accuracy remains unclear due to limited validation against patient-derived clinical data. This review collates clinical lumbar disc herniation characteristics and evaluates whether existing models replicate real-world pathology. By identifying the most morphologically relevant models, this study provides a stronger foundation for improving mechanistic herniation models.MethodsA systematic review following PRISMA guidelines identified clinical studies detailing herniation characteristics and experimental models of ex-vivo lumbar disc failure. Models were categorised by loading conditions (complex ultimate compression; cyclic; and intradiscal pressurisation), then compared to clinical data to assess their validity.ResultsIn patients, extrusions (50%) and protrusions (34%) are the most common lumbar disc herniation types, with paracentral herniations (61%) predominantly occurring at L4-L5 (49%) and L5-S1 (42%). Structural failure patterns varied, with annulus fibrosus failure reported in 35–81% of cases and endplate junction failure in 19–68%.Among 25 analysed models, all loading types induced herniations, but often with different damage patterns. Complex ultimate compression caused abrupt failures and fractures, while cyclic led to progressive annular damage. Intradiscal pressurisation highlighted nucleus pulposus migration pathways. Within a single herniation model, the damage mechanisms seen were similar between discs.ConclusionsClinical herniation patterns show significant variability, while ex-vivo models yield more repeatable outcomes. Cyclic, complex ultimate compression, and intradiscal pressurisation models provide valuable mechanistic insights but differ in physiological relevance. Researchers must consider the physiological relevance of the applied load and the differences between animal and human discs when selecting a model. Fu